Fyodor Dostoevsky’s Epilepsy: In Connection with His Novel - Khanmokhtari, Parham; Koptonashvili, Lali (European Scientific Journal, ESJ, 2022)
Fyodor Dostoevsky, aside from his intelligent structure use of epilepsy by combining it into his novels, essential idea "a moment of happiness is worth a lifetime" was perhaps stimulated by his epileptic aura. As mentioned in the article, he presented the first signs of epilepsy in early adulthood, but he was only diagnosed a decade later. For diagnosis, even Sigmund Freud, the father of psychoanalysis, theorized and wrote a book precisely for Fyodor’s condition. Later, in the modern era with the new prognosis for epileptic types, so many neurologists with constant referral on his books and novels realized Fyodor had suffered from temporal lobe epilepsy. The most influential for this comprehension was The Brothers Karamazov (1879-1880). Freud defined The Brothers Karamazov as the most powerful novel and story ever written.